URGENSI PENGEMBANGAN BAHAN AJAR BERBASIS INTERNALISASI KEARIFAN LOKAL KAMPUNG BUNGUR SEBAGAI STIMULASI KOMPETENSI EKOLITERASI PADA PEMBELAJARAN IPAS DI SD - Amaliatul Masfufah, Siti; Respati, Resa; Mohamad Setiadi, Pidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The increasing complexity of environmental issues demands early education that fosters ecological awareness. One strategic approach is strengthening ecoliteracy competencies in elementary school students. This study aims to identify the needs for developing IPAS learning materials based on the internalization of Kampung Bungur’s local wisdom to stimulate students' ecoliteracy. The research employed a descriptive qualitative method, collecting data through observation, interviews, and document studies in two partner elementary schools. The findings reveal differences in learning approaches. School A relies on teacher-centered methods and simple media, while School B adopts a participatory approach and develops its own learning materials. However, neither school has comprehensively integrated local wisdom and ecoliteracy principles into their IPAS instruction. This indicates an urgent need for contextual teaching materials that combine local wisdom with ecoliteracy to build students’ environmental awareness and encourage sustainable practices. The study recommends the development of contextual teaching materials that align with students’ daily lives and local environments to support sustainable education from an early age.